Interferensi Sintaksis Bahasa Madura Terhadap Percakapan Bahasa Arab Santri SLA - Wahyuni, Sri; Hermanto, Bambang (Jurnal Pendidikan Bahasa Arab, 2025)
This study examines the interference of the Madurese language in Arabic. The purpose of this research is to describe the forms of syntactic interference of Madurese in the Arabic conversations of students at the Syu‘bah al-Lughah al-‘Arabiyah (SLA) institution. The data consist of cases involving the omission of sentence elements, errors in phrase formation, and errors in sentence structure containing interference. A total of 16 examples were collected as data and analyzed using an error-analysis framework from a sociolinguistic perspective. The findings of the study indicate that there are four types of syntactic interference, namely changes in word formation, omission of sentence elements, errors in phrase formation, and errors in sentence structure. The contributing factors to syntactic interference include the speaker’s bilingualism and the tendency to transfer linguistic behaviors from the first language (Madurese) to the second language (Arabic). Keywords: Syntactic Interference, Madurese Language, Arabic Language.